PAKISTAN’S NATIONAL SECURITY CHALLENGES AND ECONOMIC GROWTH IMPLICATIONS FOR DEFENCE SYSTEM - Sadia Ashraf (Margalla Papers, 2025)
This paper explores the emerging challenges confronting conventional security paradigms, with a primary focus on the threats posed to the Indian Ocean Region (IOR) through an analytical framework and advancements in military technology. The manuscript examines the intricate relationship between remunerative financial stability and the state’s internal defence. The declining financial conditions pose a significant threat to various facets of societal functioning, and the reliance of national security on a robust economy is observable in the current geopolitical landscape. National security is a fundamental prerequisite for preserving state sovereignty, facilitated by strategically utilising economic resources, diplomatic engagement, military power projection, and political influence. The notion of national security is inherently dynamic, continually evolving in response to a shifting global environment. The fundamental state absorption is impossible to safeguard solely by the defence system's might, particularly when economic development is overlooked. This paper scrutinises Pakistan's deterrence strategy alongside the most significant conventional security threat posed by India, utilising a framework focused on the evolution of armament systems regarding catastrophic capabilities and enhancements in range, unmanned aerial vehicles, satellite surveillance, and other pertinent technologies. This paper examines the relationship between military fiscal allocations and economic development, considering both the presence and absence of armed conflicts (internal and external), with a focus on Pakistan and India. Ultimately, the paper examines potential strategies to address emerging security threats.